Perioperative bleeding and non-steroidal anti-inflammatory drugs: An evidence-based literature review, and current clinical appraisal. Issue 31 (31st July 2020) - Sheth, Ketan R.; Bernthal, Nicholas M.; Ho, Hung S.; Bergese, Sergio D.; Apfel, Christian C.; Stoicea, Nicoleta; Jahr, Jonathan S.
Abstract : Abstract: Patient satisfaction measures and the opioid epidemic have highlighted the need for effective perioperative pain management. Multimodal analgesia, including non-steroidal anti-inflammatory drugs (NSAIDs), have been shown to maximize pain relief and reduce opioid consumption, but are also associated with potential perioperative bleeding risks. A multidisciplinary panel conducted a clinical appraisal of bleeding risks associated with perioperative NSAID use. The appraisal consisted of review and assessment of the current published evidence related to the statement "In procedures with high bleeding risk, NSAIDs should always be avoided perioperatively." We report the presented literature and proceedings of the subsequent panel discussion and national pilot survey results. The authors' assessment of the statement based on current evidence was compared to the attempted national survey data, which revealed a wide range of opinions reflecting the ongoing debate around this issue in a small number of respondents. The appraisal concluded that caution is warranted with respect to perioperative use of NSAIDs. However, summarily excluding NSAIDs from perioperative use based on potential bleeding risks would be imprudent. It is recommended that NSAID use be guided by known patient- and procedure-specific factors to minimize bleeding risks while providing effective pain relief. Abstract : Supplemental Digital Content is available in the text